IMPACT OF THERAPEUTIC COMMUNICATION (ORIENTASI LEVEL) TO LEVEL OF FEAR DUE HOSPITALIZATION ON SCHOOL AGE CHILDREN PATIENT (6-12) YEARS, AT SERUNI ROOM, RSUD JOMBANG (Eduhealth, 2012)
ABSTRAKHospitalisasi dan saat sakit, merupakan pengalaman yang penuh tekanan bagi anak-anak. Dengan adanya komunikasi diharapkan terjadi interaksi personal antara perawat dan klien sehingga masalah-masalah yang dihadapi klien dapat terselesaikan. Tujuan Penelitian ini untuk menganalisa Pengaruh Komunikasi Terapeutik (Tahap Orientasi) Terhadap Tingkat Kecemasan pada pasien anak usia sekolah (6-12 tahun). Desain dalam penelitian ini adalah Pre-eksperimental “Static Group Comperasion” dengan populasi semua pasien usia sekolah (6-12 tahun) di Ruang Seruni RSUD Jombang. Sampelnya adalah pasien usia sekolah (6-12 tahun) dengan tehnik Convisience Sampling sebanyak 30 responden, dengan 15 responden diberikan komunikasi terapeutik (tahap orientasi) dan 15 responden sebagai kontrol. Variabel yang diteliti meliputi komunikasi terapeutik (tahap orientasi) sebagai variabel independen dan tingkat kecemasan akibat hospitalisasi pada anak usia sekolah (6-12 tahun) sebagi variabel dependen. Uji Statistik Wilcoxon nilai p=0,00. Dari hasil berarti ada perbedaan tingkat kecemasan sebelum dan sesudah diberikan komunikasi terapeutik (tahap orientasi) terhadap tingkat kecemasan akibat hospitalisai pada pasien anak usia sekolah (6-12 th). Kemudian untuk mengetahui ada pengaruh menggunakan uji Mann-Whitney ada pengaruh antara responden yang diberikan komunikasi terapeutik (tahap orientasi) dan responden yang tidak diberikan komunikasi terapeutik (tahap orientasi) di Ruang Seruni RSUD Jombang. Melihat adanya pengaruh tersebut, diharapkan para perawat lebih meningkatkan pelayanannya, khususnya dalam komunikasi terapeutik pada saat kontak atau akan melakukan tindakan pada pasien.Kata Kunci : komunikasi terapeutik, tingkat kecemasan. ABSTRACTHospitalization or during suffering the illness is such a full pressure experience for the children. Through communication, expectedly personal interaction can be occured between nurse and patients in order to have the solution for theri problems. Therapeutic communication is not only the menners of speaking softly or politely, but as well it is such a therapy. Design of the reseach is pre-experimental “Static Group Comparison” with all school population patiens aged (6-12 years) at Seruni Room, Jombang RSUD. The sample are patients whose aged (6-12 years) with convisience sampling technique, with the result 30 respondents, 15 respondents provided with communication therapeutic (orientation phase) and 15 respndents as a control. Variabel examined include therapeutic communication (orientation phase) as indendent variable dan level of fear due hospitalization on school age children (6-12 years) as dependent variable. To observe level of fear on school age children pre-provided with therapeutic communication (orientation phase), level of fear on them post-provided therapeutic communication (orientation phase), and level of fear on school age children who are not provided with therapeutic communication (orientation phase). After obtaining information, subsequently analysingthe level of fear on school age children before and after given the therapeutic communication (orientation phase) using Wilcoxon p=0.000. From the result, which means there is the difference of fear level before and after therapeutic communication treatment (orientation phase) to level of fear due hospitalization school age children patient (6-12 years). And then to identify that there is the effect of using Mann-Whitney p=0.000, which means there is the effect between the respondent who is treated an untreated with therapeutic communication (orientation phase) at Seruni Room, Jombang RSUD. According to those effects, hoped that the nurses can be more capable and focus on their services, specifically in therapeutic communication during contact or about to do further action on patients.Key words : level of fear, therapeutic communication